Does The Age Influence Intention to Switch to Sharia Banking Services: A Case Study of Islamic Bank Customers in Indonesia - Azis, Elvira; Ratih Hurriyati; Heny Hendrayati; Hilda Monoarfa; Muhammad Fatwa F (Jurnal Manajemen Indonesia, 2024)
This study examined the moderating effect of age on switching intention among Islamic bank customers in Indonesia who also hold accounts in conventional banks using the push, pull, and mooring approach. A quantitative research approach was adopted using Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis with a sample of 324 respondents. The findings revealed that the Push, Pull, and Mooring approach significantly affect switching intention. Specifically, dissatisfaction and regret were identified as key components of the push factor, religious motivation represented the mooring factor, and alternative attractiveness and subjective norm were central to the pull factor. Age emerged as a critical moderating variable. The mooring factor had a significant impact on customers aged 35–45 years, while the push factor was more influential among younger customers (17–35 years) and those above 45 years. In contrast, the pull factor consistently affected switching intention across all age groups. These results provide practical insights for decision makers in planning targeted marketing strategies and contribute to the marketing management literature, particularly in the context of Islamic banking.